Ginger extract (Zingiber officinale) triggers apoptosis and G0/G1 cells arrest in HCT 116 and HT 29 colon cancer cell lines - Abdullah, Shailah (Academic Journals, 2010)
Although many studies have shown the antitumor properties of ginger extract (Zingiber officinale), little is known regarding the mechanism of its effects. This study was conducted to determine the mechanism of antitumor effects of ginger extract by evaluating apoptosis rate and cell cycle progression status in colon cancer cell lines HCT 116 and p53 defective HT 29. HCT 116 and HT 29 cells were cultured in the presence of ginger extract at various concentrations for 24 h. The percentage of cell viability was determined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-di phenyl tetrazolium bromide (MTT) assay. Our results showed that ginger extract inhibited proliferation of HCT 116 and HT 29 cells with an IC50 of 496 ± 34.2 µg/ml and 455 ± 18.6 µg/ml, respectively. We also found that ginger extract at increasing concentrations induced apoptosis dose dependently in both colon cancer cells. Apoptosis rates were 11.15, 35.05 and 57.49% for HCT 116 and 4.39, 19.81 and 28.09% for HT 29 at 200, 500 and 800 µg/ml of ginger extract, respectively. Ginger extract arrested HCT 116 and HT 29 cells at G0/G1 and G2/M phases with corresponding decreased in S-phase. This study suggests that ginger extract may exert its antitumor effects on colon cancer cells by suppressing its growth, arresting the G0/G1-phase, reducing DNA synthesis and inducing apoptosis.